COHESION AND COHERENCE IN ACADEMIC WRITING: LINGUISTIC MECHANISMS AND COMMUNICATIVE FUNCTIONS (Ustozlar uchun, 2026)
Cohesion and coherence are crucial aspects of effective academic writing. Cohesion refers to the grammatical and lexical tools that link sentences and clauses. Coherence relates to how ideas are organized logically and how clear the meaning is in a text. This article looks at the linguistic tools that create cohesion, such as reference, substitution, ellipsis, conjunction, and lexical cohesion. It also discusses coherence as a cognitive and rhetorical concept shaped by logical structure, thematic flow, and reader expectations. Drawing on functional linguistics and discourse analysis, particularly the work by M. A. K. Halliday and Ruquaiya Hasan, this study shows how cohesive tools and coherent organization work together to create effective academic writing.